Professional Survival in Teaching English in Indonesia - Prijambodo, V. Luluk (English Education Department, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya, 2017)
Teaching English as a foreign language (TEFL) in Indonesia offers not only challenges but also reward. Some teachers perceive the challenges as the professional consequences for their determination to be English teachers. Such a perception leads them to the enjoyment and optimism toward their sustainable professional development or career escalation. Some others consider the challenges as such a heavy burden of life that they feel unmotivated to elevate their professional development. In this era of education standardization, teachers are faced with two dichotomous options: satisfying the standard optimally in order to deserve the professional rewards or benefits or just fulfilling it minimally and accordingly miss the career advancement and the professional reward. This paper shares the ideas of what English teachers need to do to survive professionally in their English teaching and gain the professional benefits offered.